Sensitivitas Kesetaraan Gender terhadap Mahasiswa Baru Tahun 2023 Universitas Pendidikan Indonesia - Nur Cahayu Baitunnisa; Hikmalia Safitri; Supriyono Supriyono (FKIP, Universitas Palangka Raya, 2025)
Gender inequality is a social injustice that distinguishes men and women in society. Inequality from the gender aspect is a hot issue in many circles, one of which is among campus students. The purpose of this study is to determine the understanding of the concept of gender equality among new students of Universitas Pendidikan Indonesia to be applied in student life, especially in the field of education. This study used a descriptive quantitative and survey approach. The study involved 136 new students from eight faculties at Universitas Pendidikan Indonesia. Data were collected through the use of a closed-ended questionnaire that could be accessed through a Google form link. A simple random sampling method was used to distribute the questionnaire to new students in each department online. The results of this study indicate that new students of Universitas Pendidikan Indonesia still encounter many cases of gender discrimination in the campus environment, and the results show that they understand and partly take part in the manifestation of gender equality.